A revised area taxonomy of phytogeographical regions within the Australian Bioregionalisation Atlas - Ebach, Malte C.; González-Orozco, Carlos E.; Miller, Joseph T.; Murphy, Daniel J. (Phytotaxa, 2015)
The phytogeographical regions and sub-regions of Australia are revised in light of new data from a recent analysis by González-Orozco, Ebach et al. (2014). The new revision includes two new regions, Northern regio nova and Northern Desert regio nova, and five new sub-regions, Nullarbor sub-regio nova, Central Desert sub-regio nova, Great Sandy Desert Interzone sub-regio nova, Central Queensland sub-regio nova and, Southwestern sub-regio nova. This new revised version of the phytogeographical regions and sub-regions of Australia’s land plants provides an updated classification based on historical nomenclature. The analysis by González-Orozco, Ebach et al. (2014) is a biogeographically centered classification that generated the first exclusively taxonomic regionalisation of Australia’s land plants, used here to update the ABA phytogeographical regions.